Transparent fuzzy logic based methods for some human resource problems - Canós-Darós, L.; Canós-Darós, M. J.; Fuller, R (Rect@, 2012)
Personnel selection and reallocation are human resources policies that should be planned andimplemented accurately because of their importance to the future of the company. When a person is hired, he or sherepresents an investment in human capital. This is the reason because managers have to use different tools in order tomake good decisions. In this paper we present some fuzzy tools for personnel selection and reallocation processes andthe advantages and disadvantages of their applying. Moreover, we show some examples, including the use of a specific software.